Kolaborasi Bahasa, Seni, Sastra, dan Budaya dalam Produksi Rumah Budaya Multikultural Berbasis Ekonomi Kreatif untuk Peningkatan Income Generating - Endraswara, Suwardi; Widyastuti, Sri Harti; Ekowati, Venny Indria (Balai Bahasa Sulawesi Selatan, 2025)
This research aims to prepare the production of multicultural cultural houses to increase UNY's income generation from a creative economy perspective. This effort is expected to support UNY's vision and mission as a world-class university while simultaneously increasing UNY's income generation in the era of PTNBH (State-Owned Legal Entities). The production of multicultural cultural houses is realized through collaboration between study programs within the Faculty of Social and Political Sciences (FBSB) UNY, utilizing the potential of local language, art, literature, and culture that are marketable as creative economy commodities. This study utilizes the theory of exploratory and collaborative cultural house production development, related to the empowerment of local language, art, literature, and culture. The research method used is qualitative, encompassing heuristic, exploratory, and negotiative approaches, which serve as analytical tools to develop Javanese cultural entrepreneurship packages as a competitive advantage. The results indicate that the production of multicultural cultural houses can be achieved through two steps. First, the development of a pranatacara package that utilizes panyandra practices, which are related to the ethnomathematic concept of spiritual hydrology, is realized through the empowerment of macapat songs in the siraman manten tradition. Second, the empowerment of collaborative elements of language, art, literature, and culture from an ethnobotanical perspective in the Panggih Manten tradition, where panyandra is embodied in the form of parikan (pantun) and macapat songs combined with gending (traditional music). AbstrakPenelitian ini bertujuan menyiapkan produksi rumah budaya multikultural untuk meningkatkan income generating UNY dalam perspektif ekonomi kreatif. Upaya ini diharapkan mampu mendukung visi dan misi UNY sebagai world class university sekaligus meningkatkan income generating UNY di era PTNBH. Produksi rumah budaya multikultural diwujudkan melalui kolaborasi antarprogram studi di lingkungan FBSB UNY, dengan memanfaatkan potensi bahasa, seni, sastra, dan budaya lokal yang layak jual sebagai komoditas ekonomi kreatif. Kajian ini menggunakan teori pengembangan produksi rumah budaya secara eksploratif dan kolaboratif, yang berkaitan dengan pemberdayaan karya bahasa, seni, sastra, dan budaya lokal. Metode penelitian yang digunakan bersifat kualitatif, mencakup heuristic, eksploratif, dan negosiatif, yang berfungsi sebagai alat analisis untuk menghasilkan paket wirausaha budaya Jawa sebagai keunggulan kompetitif. Hasil penelitian menunjukkan bahwa produksi rumah budaya multikultural dapat ditempuh melalui dua hal. Pertama, pembentukan paket pranatacara yang memanfaatkan praktik panyandra, yang terkait dengan konsep etnomatematika hidrologi spiritual, diwujudkan melalui pemberdayaan tembang macapat dalam tradisi siraman manten. Kedua, pemberdayaan unsur kolaborasi bahasa, seni, sastra, dan budaya dalam perspektif etnobotani budaya pada tradisi panggih manten, di mana panyandra diwujudkan dalam bentuk parikan (pantun) dan tembang macapat yang dikolaborasikan dengan gending.